Is weight loss surgery right for you? - Apple, Robin F. (Robin Faye) (Oxford University Press, 2006)
Obesity has quickly become an American epidemic. If you are suffering from significant overweight and the problems that go along with it, you may be contemplating weight loss surgery. The decision to pursue weight loss surgery should not be taken lightly. There are many factors to consider. This book contains all the need-to-know information about weight loss surgery and how to decide whether or not it is right for you. Is Weight Loss Surgery Right for You? helps guide you through the decision-making process by providing information on the various types of bariatric surgery available, their re.